1954
DOI: 10.1172/jci103011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Infusion of Hyperoncotic Dextran in Children with the Nephrotic Syndrome1

Abstract: Dextran is a bacterial polysaccharide which is being increasingly used as a plasma substitute (1-4). Dextran molecules frequently have a molecular weight of several million, and consist of long branched chains of glucose units. For clinical use these large molecules are broken down artificially to an average molecular weight of 70,000. In the body, the larger molecular aggregates are further broken down and excreted as smaller fractions having (approximate) molecular weights less than 20,000, or are slowly met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1957
1957
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Dextran caused no complications except for oliguria following the infusions in the third patient. Proteinuria increased significantly during two courses of dextran, in accord with previous observations (13). (14), malnutrition (15), kwashiorkor (16), or the hypercatabolic type of idiopathic hypoalbuminemia (17) in which low levels of serum albumin occur.…”
Section: Effects Of Albumin Infusionssupporting
confidence: 90%
“…Dextran caused no complications except for oliguria following the infusions in the third patient. Proteinuria increased significantly during two courses of dextran, in accord with previous observations (13). (14), malnutrition (15), kwashiorkor (16), or the hypercatabolic type of idiopathic hypoalbuminemia (17) in which low levels of serum albumin occur.…”
Section: Effects Of Albumin Infusionssupporting
confidence: 90%
“…(24), however, from calculations of albumin clearances and minimum concentrations of albumin in the glomeru lar filtrate in nephrotic subjects given albumin infusions, concluded that proteinuria was the result of increased permeability only. James et al (25), using dextran infusions, came to the same conclusion. Lauson et at.…”
mentioning
confidence: 69%
“…The clinical utility of non-albumin colloids, such as (hyperoncotic 12% dextran solution given at 1.2–1.8 g/kg body weight daily as a single dose or on 3–5 consecutive days), was previously investigated in children with nephrotic edema ( 59 ). The precise mechanism of action has not been clarified.…”
Section: Pharmacological Management Of Nephrotic Edemamentioning
confidence: 99%